Evaluation of commercial von Willebrand factor collagen binding assays to assist the discrimination of types 1 and 2 von Willebrand disease - Favaloro, Emmanuel J. (Thrombosis and Haemostasis, 2010)
This study reports on the evaluation of seven commercial von Wille-brand factor (VWF) collagen binding (VWF:CB) assays to potentially assist the discrimination of types 1 and 2 von Willebrand disease (VWD). Samples from 25 patients with type 1 VWD, of varying severity, were co-tested with 16 samples from patients with types 2A or 2B VWD, plus various control samples, using each commercial VWF:CB assay assessed against our standard (reference) in-house VWF:CB assay, as well as our in-house VWF antigen (VWF:Ag) and ristocetin cofactor (VWF:RCo) assays. Commercial VWF:CB assays varied in their ability to discriminate types 1 and 2A/2B VWD. The optimal VWF:CB/VWF:Ag ratio at which optimal discrimination occurred also differed between assays, with some improvements observed with some (but not all) as-says following a harmonisation process that aimed to correct for different calibrator effects. Assay variability also compromised assay utility in some test occasions. Future standardisation and improvements in some commercial VWF:CB assays are needed before the VWF:CB assay can be more fully and globally utilised for discrimination of VWD types in diagnostic laboratories.
Keywords: von Willebrand factor; VWF; collagen binding; von Willebrand disease; VWD; diagnosis